5.3k views
3 votes
Givin that f(x)=x squared -3x+3 and g(x) = x-1/4 solve for f(g(x)) when x is 5

User Langsmith
by
5.5k points

2 Answers

4 votes

f(x)=x²-3x+3

g(x)=x-1/4

f(g(x))=f(x-1/4)

replacing x by x-1/4 in the function f(x),

f(g(x))=(x-1/4)²-3(x-1/4)+3

we have to find its value when x is 5, so

f(g(5))=(5-1/4)²-3(5-1/4)+3

= (4.75)²-14.25 +3

=22.5625 -11.25

f(g(5)) = 11.3125

User Rabid
by
5.8k points
1 vote

Here,


f(x) = x^2 -3x+3 , g(x) = (x-1)/(4)

And we need to find the value of f(g(x)) when x = 5 . It means , we need to find f(g(5)) .

So first we need to find g(5) and for that we plug 5 for x in g(x). That is ,


g(5)=(5-1)/(4)=1

So the value of g(5) is 1 .

Now we have f(g(5)) = f(1) . And f(1) is


1^2 -3(1)+3 = 1

So the value of f(g(5)) =1

User Sandover
by
6.1k points